Cress - Meyer, Marissa (New York : Feiwel and Friends, an imprint of Macmillan, 2014)
Cinder and Captain Thorne are fugitives on the run, now with Scarlet and Wolf in tow. Together, they're plotting to overthrow Queen Levana and prevent her army from invading Earth. Their best hope lies with Cress, a girl trapped on a satellite since childhood who's only ever had her netscreens as company.
840
Keywords: Cyborgs -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Teenage girls -- Juvenile fiction; Queens -- Juvenile fiction; Science fiction